TAL1 overexpression in induced pluripotent stem cells promotes the formation of hematopoietic cell-forming complexes but inhibits enucleation in vitro - Shin, Arim; Park, Sung Ah; Kim, Ji Yeon; Baek, Eun Jung (Frontiers in Cell and Developmental Biology, 2025)
The in vitro generation of human red blood cells (RBCs) from stem cells, such as induced pluripotent stem cells (iPSCs), holds promise for transfusable RBCs but faces challenges, including RBC maturation, enucleation, and large-scale production. In this study, we evaluated the effect of conditional TAL1 overexpression on in vitro RBC production via hematopoietic cell-forming complex (HCFC) formation from iPSCs because TAL1 is a key regulatory transcription factor essential for erythropoiesis. TAL1 overexpression in iPSCs, either before or after hematopoietic induction, significantly enhanced HCFC formation and hematopoietic differentiation, as evidenced by increased hematopoiesis-related gene expression, a higher yield of glycophorin A (GPA)+/CD71+ cells, and elevated gamma hemoglobin levels. These findings highlight the potential of TAL1 as a powerful regulator of erythropoiesis in vitro and offer a promising strategy for improving RBC production from stem cells. However, the reduced enucleation efficiency observed after TAL1 overexpression indicates a key challenge that must be addressed to optimize the generation of fully functional, transfusable RBCs. Further research is required to balance the benefits of enhanced differentiation with the need for efficient enucleation, which is critical for the production of mature, viable RBCs.